The Standard of Living and Its Dimensions in NUTS–4 Districts in Poland. An Analysis of Diversification - Dańska-Borsiak, Barbara (Acta Universitatis Lodziensis. Folia Oeconomica, 2022)
Along with an increase in the level of societies’ wealth, factors such as the state of health, the quality of education and negative output effects including environment quality are becoming increasingly important in assessing the standard of living and well‑being of the average person. A category that has long been used to measure the economic and social well‑being of societies is GDP per capita. However, in contemporary research, other attempts, more comprehensively describing important aspects of life, are being proposed. The main aim of this article is to examine the standard of living in NUTS–4 districts in Poland in 2020 in aggregate and in its particular dimensions. Spatial differentiation of the standard of living index and sub‑indices describing its individual dimensions was also examined. The standard of living was measured on the basis of a composite variable. This variable was constructed as Hellwig’s measure of economic development on the basis of values of partial indicators describing successive dimensions. Those indicators were determined as arithmetic means of normalised diagnostic variables. The highest standard of living is observed in cities with powiat status. Among them, there are both the largest agglomerations and smaller cities constituting local centres. In the spatial distribution of the standard of living measure, attention is drawn to the large concentration of districts with the lowest values in the north‑east of Poland, in the Kujawy Region and in the south‑east. Partial indicators describing the dimensions of the standard of living, constructed for the purposes of the study, reflect the situation with regard to the degree of implementation of detailed tasks of social policy. The analysis of the situation of districts in particular dimensions of the standard of living carried out in this paper makes it possible to indicate the districts that require the greatest attention of decision‑makers and to direct the greatest resources to them.